Figuren der Urszene Material und Darstellung in der Psychoanalyse Freuds - Klammer, Markus (Turia und Kant, 2013)
In Freudian psychoanalysis the so-called »primal scene« is of a very fragile ontological and epistemological nature. It oscillates between factual event, phylogenetically pre-structured phantasy and construction of the analyst. The book examines Freud's arguments for and against the reality of the primal scene by way of his famous case study »Aus der Geschichte einer infantilen Neurose«. It employs methods from the history of science to address philosophical, epistemological, aesthetic, and political questions. Apart from analyzing Freud's arguments themselves and their metaphorical vehicles, it examines the first edition of the case study and also takes into account the manuscript in the Library of Congress in Washington. Both sources have been heretofore neglected by Freud scholars.